Evaluation of the Infection Risk in Dialysis and Chronic Kidney Disease Patients Using an ATP Monitoring Assay. Issue 3 (13th March 2017) - Kusano, Junichi; Kato, Rei; Matsuda, Hiroto; Hara, Yoshikazu; Fujii, Yoshiaki; Suzuki, Shinya; Sekiyama, Masao; Ando, Eiki; Sugiyama, Kentaro; Hirano, Toshihiko
Abstract: The ATP monitoring assay is a useful biomarker for risk monitoring to detect infection and rejection episodes in transplant recipients. Hemodialysis patients have a higher rate of infectious mortality. Infections in hemodialysis patients are mainly caused by venous catheters, uremia, malnutrition and inflammation. However, the risk of infection episodes has not been evaluated using a lymphocyte ATP monitoring assay in hemodialysis and chronic kidney disease (CKD) patients. We measured the ATP amounts in the peripheral CD4+ cells of CKD ( N =  85) and dialysis patients ( N =  17) using an "Immuknow" assay kit. These CKD patients were divided, according to kidney disease stage, into G3a, G3b, G4, and G5 groups. The ATP amounts in CD4+ cells of the dialysis patients and each of the CKD groups were compared with healthy subjects. In both the dialysis and CKD patients, the ATP amounts in CD4+ cells were lower than in healthy subjects. Furthermore, there were significant differences in the ATP amounts between healthy subjects and each of the CKD‐G3a, CKD‐G3b, and CKD‐G4 groups ( P  < 0.05). Patients with CKD‐G3a, CKD‐G3b and CKD‐G4 were evaluated as being at high risk for infection according to the lymphocyte ATP monitoring assay. However, the ATP amounts in the dialysis and CKD‐G5 patients did not differ from those in healthy subjects to a statistically significant extent. These results suggest that the ATP amount in the CD4+ cells of these patients with serve renal failure are influenced by dialysis treatment, uremia and/or oxidative stress.